PENGAJARAN TEOLOGI PADAANAK USIA DINI MELALUI LAGU TRI MURTI (NYANYIAN DHARMA) - Utami Dewi, Ida Ayu Putu (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2017)
Early childhood education is the main gateway in entering the next education. Conducting education as early as possible is an investment in further education as well as building a solid foundation of life. This period is a very important period, where at this time the human experience full development, so called as the golden age. Teaching theology can be done through songs. Chanting of children’s songs is a powerful weapon in building theological values towards the children. They can learn about the theological value contained in the song while they are singing happily. One of the Hindu children’s songs is Tri Murti. This Tri Murti song indirectly adds positive stimulus to the growth of the child. The lyrics of the song imply the concept of divinity in Hinduism with language that is easily understood by young children without having to peel deeper. Where the God of Hinduism has three main manifestations consisting of the Lord Brahma, Lord Vishnu and Lord Shiva are referred to as the three main devātas. These three gods are described as having different tasks and mastering different elements and different scriptures. With this song, young Hindu youths have been installed early on in theology and need not worry about other people’s accusations that Hindus worship a lot of God; Hinduism is a religion of polytheism and so on. In this song is very clearly mentioned that there are three manifestations of God called Tri Murti with different names, different characters, and different tasks. However, in essence, it is one that is Brahman.